LA RADIO EN EL OTRO LADO DEL TIEMPO - Alicia TAPIA LÓPEZ (Fonseca, Journal of Communication, 2023)
On October 30, 1938, Orson Welles aired the radio drama The War of the Worlds on the CBS Radio network, adapting the science-fiction novel by the British writer H. G. Wells. During the broadcast, listeners became stricken with panic, believing that the Earth was actually being invaded by giant snake-like Martians launching rays of fire down on humans